2013
DOI: 10.1007/s11604-013-0205-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoma feeding arteriogram created by CT during aortography using IVR 64-multidetector-row CT for catheterization in transcatheter arterial chemoembolization for hepatocellular carcinoma

Abstract: CT during aortography (CTAo) using IVR 64-multidetector-row CT (IVR-64MDCT) enables the rapid and simultaneous depiction of both the hepatic and extrahepatic feeding arteries in hepatocellular carcinoma (HCC), and can be achieved using a reasonable volume of contrast medium. The scan time is approximately 6 s from the diaphragm to the kidney using CTAo with 64MDCT with a slice thickness and slice interval of 0.5 mm. The hepatoma feeding arteriogram appears in the angiographic monitor after CTAo, and can then b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…There is a possibility that tumor‐feeders arising from other arteries or the aorta may remain other than the embolized branches. CT during aortography may be useful to detect all tumor‐feeders from the hepatic and extrahepatic collateral vessels; however, it may require a large amount of contrast material. Third, TACE through the cystic, right colic and left gastric arteries was performed with complete confidence in AFD.…”
Section: Discussionmentioning
confidence: 99%
“…There is a possibility that tumor‐feeders arising from other arteries or the aorta may remain other than the embolized branches. CT during aortography may be useful to detect all tumor‐feeders from the hepatic and extrahepatic collateral vessels; however, it may require a large amount of contrast material. Third, TACE through the cystic, right colic and left gastric arteries was performed with complete confidence in AFD.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, combined CTHA and CTAP can outperform diagnostic CT (25,26) and affect choice of treatment, especially in those patients presenting with HCC recurrence (25) (Fig 2). The use of CTHA and CTAP during transarterial hepatic therapy procedures has been demonstrated to be a highly sensitive method not only to identify liver tumors and their hepatic feeding arteries but also to detect important extrahepatic feeding arteries (27,28) and hepatic arterial variations (Fig 3). Ozaki et al analyzed the visualization of extrahepatic feeding arteries at digital subtraction angiography (DSA) and CTHA; they reported that use of CTHA resulted in higher frequencies of detection of extrahepatic arterial branches than DSA (98.0% vs 40.6% for the same 943 patients) (29).…”
Section: Imaging Performance Of Angio-ct Systemsmentioning
confidence: 99%
“…The protocol used for MDCT-AA follows that for detecting the feeding artery for hepatocellular carcinoma described in a previous report (Minamiguchi et al [2013]). In short, a 3 F pigtail catheter (70 cm, Medikit) was advanced so that its tip was positioned at the level of the tracheal bifurcation.…”
Section: Reviewmentioning
confidence: 99%
“…The hemorrhage-responsible arteriogram is created on the same basis as that reported for a hepatoma-feeding arteriogram (Minamiguchi et al [2013]). In short, the hemorrhage-responsible arteriogram using MDCTAo is synthesized using three basic VR images: a background bone VR image, an aorta–branch artery VR image, and a hemorrhage–responsible artery VR image.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation